Dollar Dash / Syafiqah Mohd Shazwan Sam ... [et al.] - Mohd Shazwan Sam, Syafiqah; Ghazali, Risha Daleina; Julius, Magdalen; Mohd Latiff, Aliah Iman; Mohd Nor, Amirudin (Universiti Teknologi MARA, Kedah, 2023)
The innovation that we intended to introduce is called Dollar Dash. We have improvised the Snake and Ladder game by adding mathematics and financial elements that could be very interesting for all ages. Such improvement, inspired by the game-based teaching and learning methodology, is specifically designed to cater to the learning aspects of the players, particularly the students. Students frequently struggle with calculation subjects and easily lose interest when it comes to complicated equations with unclear methods and formulas. The boredom and negative feelings will discourage students from studying as it does not fit their desired learning method. Hence, the objective of improvising the board game is to assist students to grasp the learning content of the related mathematical and financing subject through interactive games. In short, the players can learn while playing the said game. In essence, the game creates a mix between teaching and enjoyment, keeping players interested the entire time. Dollar Dash calls for strategic judgment, analytical thinking, and problem-solving abilities. This engaging game offers a comprehensive overview of financial knowledge. We have targeted three main communities that could benefit from our game in which; primary students can strengthen their basic calculations, university students can enhance their financial knowledge and educators can also use the board game as their teaching aids to make the learning content more enjoyable. With Intellectual Property (IPO) application underway, we foresee a potential commercial collaboration with industry players. Future plans include converting this physical board game into a digitalized online game to cater to tech-savvy students.